The Correlation between Parent’s Understanding with Their Participation for Joining the Parenting Program in Early Childhood Education - Rizky Suwandi; Wisroni Wisroni (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2019)
This research was motivated by a lack of parental participation in parenting activities in PAUD Sinar Gunung, Padang City. This lack of parental participation is thought to lack understanding about parenting. This study aims to (1) describe the understanding of parents, (2) describe the participation of parents and (3) see the relationship between understanding and parenting participation in parenting programs.This type of research uses correlational quantitative methods. The population in this study were 25 parents who interacted directly with educators and registered their children in the PAUD Sinar Gunung institution. Samples were taken as much as 60%. The number of samples is 15 people. The sampling technique uses simple random sampling. Data collection techniques used were questionnaires and test questions in the form of questionnaires, while data collection tools in the form of a list of statements and questions. The data analysis technique of this study uses percentage and rank orders.The results of the study can be seen that (1) parents 'understanding of parenting programs is still low, (2) parental participation in parenting activities is still low, and (3) there is a significant relationship between parents' understanding of parenting programs and their participation in activities parenting.Keywords: Parents Understanding, Participation, Parenting Program